(untitled) (Revista Argentina de Musicología, 2018)
Like other societies of the indigenous world, the jalq ’a and tarabuco from the Sucre region use their musical practices to define gender difference; to set the boundary between masculine and feminine. Thus, there is a gender distribution of the musical roles where men -except in some rituals- play the instruments and women sing. Although men al so sometimes join in the singing, the aesthetic ideal is in the women ’s high pitched voices. A first glance al feminine vocal practices reveals that these are associated with the life cycle and divide it large stages. Through their singing. women move from a wild untamed time and space towards the socialized world of culture. a journey that, al the same time. plays an essential role in the elaboration of femininity.